Delineating the Challenges and Remedies of the School Management Committees as Constituted under RTE Act 2009 - Vikram Kumar (JOURNAL OF INDIAN EDUCATION, 2018)
The present article brings forth the challenges and suggestions in the context of functioning of the School Management Committee (SMC) in the schools of the Directorate of Education, Government of National Capital Territory of Delhi (GNCTD) as constituted under the Right to Education Act (RTE), 2009. Broadly speaking, the RTE Act has recommended the major functions to be performed by the SMC in schools which include monitoring the school functioning, preparing and recommending the ‘School Development Plan (SDP)’, and monitoring the utilisation of grants. Although, the RTE Act, 2009 has enlisted the responsibilities of the SMC in the functioning of schools, it did not elaborate on aspects such as monitoring, ensuring, bringing to notice, etc. Hence, numerous challenges were encountered by the SMC members in schools like lack of awareness regarding the roles and responsibilities, lack of participation of the parent members in SMC, lack of clarity about funds and finances for SMC, etc. However, over the past few years, the Delhi government has initiated several reforms in the area of the school management committee to facilitate the functioning of SMCs in the schools of DoE, GNCTD. The Delhi government has worked extensively to strengthen the functioning of SMCs through many new initiatives like organising ‘Capacity Building Programmes’, ‘Reading Mela’, ‘Mega PTMs’, ‘SMC Sabha’, ‘SMC App’, ‘Mission Buniyad’, etc., to involve all stakeholders in the education of children.